Etos Kerja Dan Perilaku Islami Para Pedagang Kios Taman Wisata Candi Borobudur - Sulistiyo, Rozib; Kuswandi, Dedi; Idi, Abdullah; Syawaluddin, Muhammad (Universitas Cokroaminoto Yogyakarta, 2023)
This research is a field research conducted by taking a sample of traders' qualitatively. This study was approached with an emphasis on the social and cultural relations. According to Parson, there are four important functions that must be considered, namely AGIL (A) Adaptation, (G) Goal Attainment, (I) Integration, and (L) Latency. In this study, social and cultural relations will be examined by the “kios” traders at the Borobudur Temple Tourism Park on the meaning, understanding and appreciation of Islamic values in their trading process. it can be concluded that the Islamic behavior of TWCB’s “kios” traders is reflected in their lifestyle in line with the understanding of the beliefs and environmental traditions of the local community. The manifestation of this behavior is reflected in personal and communal behavior.